O silêncio que me Toca: efeitos de sentido, silenciamento e constituição do sujeito da Toca - Silva, Guilherme Araujo (2017)
Toca is the name traditionally used to name a rural afrodescendant community, located in Paulo Lopes' city, about 70 kilometers from the capital state , Florianópolis. In this work, it was analyzed a way of changing from (Toca), to Santa Cruz, this process of (re) naming / deletion is simultaneous with another one, the silencing of afrodescendant subjects in that community. Corpus of analysis was composed by multiple documents produced about the Paulo Lopes' afrodescendants, included official letters, baptism records, state newspaper ads, television news, printed reports and bibliographies about Paulo Lopes (HEERDT, 1988, MACHADO, 1993 and Geremias, 2003) and also Desterro - now Florianópolis' city (CARDOSO, 2000, PIAZZA, 1975a, 1975b, 1982). Similarly, interviews were made with the five oldest residents in that community, as well a investigation of 25 profiles on Facebook in search of statements produced by them. The system used to research was built based on the theoretical and analytical scope of Discourse Analysis of the French language (AD). Historically submitted to a servitude work way, afrodescendant from that community did not make by themselves, written documents. The Toca, which in the oral speech, designates the place and its inhabitants - the place of the blacks in Paulo Lopes - after a effective action of the Catholic Church, was named Santa Cruz. After this, the entire process of land regularization, by INCRA, to regulate the community as a quilombo, takes this denomination (Santa Cruz) as a reference. The processes analyzed have led to the erasure / silencing the subject-form, typical oral discourse, of afrodescendants from region slaves. This analysis allowed us to show, in this way, the subjects inside the institutionalition of the Santa Cruz quilombo.